Polyphasic Identification and Genomic Insights of Leptothermofonsia sichuanensis gen. sp. nov., a Novel Thermophilic Cyanobacteria Within Leptolyngbyaceae - Tang, Jie; Shah, Mahfuzur R.; Yao, Dan; Jiang, Ying; Du, Lianming; Zhao, Kelei; Li, Liheng; Li, Meijin; Waleron, Michal M.; Waleron, Malgorzata; Waleron, Krzysztof; Daroch, Maurycy (Frontiers in Microbiology, 2022)
Thermal environments are an important reservoir of thermophiles with significant ecological and biotechnological potentials. However, thermophilic isolates remain largely unrecovered from their habitats and are rarely systematically identified. In this study, we characterized using polyphasic approaches a thermophilic strain, PKUAC-SCTAE412 (E412 hereafter) recovered from Lotus Lake hot spring based in Ganzi prefecture, China. The results of 16S rRNA/16S-23S ITS phylogenies, secondary structure and morphology comparison strongly supported that strain E412 represent a novel genus within Leptolyngbyaceae. This delineation was further confirmed by genome-based analyses (phylogenomic inference, average nucleotide/amino-acid identity and the percentages of conserved proteins). Based on the botanical code, the isolate is herein delineated as Leptothermofonsia sichuanensis gen. sp. nov, a genus adjacent to recently delineated Kovacikia and Stenomitos. In addition, we successfully obtained the first complete genome of this new genus. Genomic analysis revealed its adaptations to the adverse hot spring environment and extensive molecular components related to mobile genetic elements, photosynthesis and nitrogen metabolism. Moreover, the strain was capable of modifying the composition of its light-harvesting apparatus depending on the wavelength and photoperiod, showing chromatic adaptation capacity characteristic for T1 and T2 pigmentation types. Other physiological studies showed the strain's ability to utilize sodium bicarbonate and various sulphur compounds. The strain was also shown to be diazotrophic. Interestingly, 24.6% of annotated protein-coding genes in the E412 genome were identified as putatively acquired, hypothesizing that a large number of genes acquired through HGT might contribute to the genome expansion and habitat adaptation of those thermophilic strains. Most the HGT candidates (69.4%) were categorised as metabolic functions as suggested by the KEGG analysis. Overall, the complete genome of strain E412 provides the first insight into the genomic feature of the genus Leptothermofonsia and lays the foundation for future global ecogenomic and geogenomic studies.